Proses Berpikir Mahasiswa Dalam Menyelesaikan Soal Kombinatorial Berdasarkan Kecerdasan Logis Matematis - Lilia Sinta Wahyuniar; Santi Widyawati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2017)
The thinking process of each student varies in solving mathematical problems. The process of thinking in this study are grouped into three conceptual thought process, semikonseptual, and computational. The objectives of this research are to investigate the thinking process of IT student with the high logical-mathematical intelligence in solving kombinatorial problems, the thinking process of IT student with the moderate logical-mathematical intelligence in solving kombinatorial problems, the thinking process of IT student with the low logical-mathematical intelligence in solving kombinatorial problems. This research is descriptive qualitative whichdescribes the process of thinking of students in solving mathematicalproblems on material kombinatorial. The data collection method in this study using tests and interviews. Subjects of this study were six students from 1D grade IT of Universitas Nusantara PGRI Kediri and represented two student with the high logical-mathematical intelligence, two student with the moderate logical-mathematical intelligence and two student with the low logical-mathematical intelligence. Data analysistechnique used Miles and Huberman, data reduction, display, andconclusion drawing / verification. Based on the analysis we concluded thatstudents with high logical-mathematical intelligence haveconceptualthought process, the thinking process of student with the moderate logical-mathematical intelligence no identified, students with low logical-mathematical intelligence have computationalthought process.